Sex for Life : From Virginity to Viagra, How Sexuality Changes Throughout Our Lives - DeLamater, John D.; Carpenter, Laura M. (Book collections on Project MUSE., 2012)
Sexual beliefs, behaviours and identities are interwoven throughout our lives, from childhood to old age. An edited collection of original empirical contributions united through its use of a distinctive, cutting-edge theoretical framework, Sex for Life critically examines sexuality across the entire lifespan. Rooted in diverse disciplines and employing a wide range of research methods, the chapters explore the sexual and social transitions that typically map to broad life stages, as well as key age-graded physiological transitions, such as puberty and menopause, while drawing on the latest developments in gender, sexuality, and life course studies.